Penilaian Kecekapan Pengutipan Sisa Pepejal di Malaysia Satu Kajian Kes di Majlis Perbandaran Seremban - Kasbi, Noor Rasidah; Ghazali, A. Wahid; Hassan, M. Nasir (Universiti Putra Malaysia Press, 1995)
The efficiency of solid waste collection is influenced by the type of vehicle used, methods of collection and the type of area served with the r2 values equal to 100%. Mechanical collection with a lifter has been proven to be the most efficient (0.39 minute/lot) compared to manual collection by open lorry which is the least efficient (5.11 minute/lot). In terms of area served, collection of waste in residential areas is the most efficient at about 0.19 minute/lot. The semimechanical collection method is relatively cheaper (RM415,720/lorry.year) than manual collection (RM435,290/lorry.year). In addition, the collection of solid waste by private agencies is relatively cheaper than collection by government agencies.